Korelasi Tasawuf Akhlaqi, Irfani dan Falsafi: Antara Abdul Qadir al-Jilani, Rabi’ah al-‘Adawiyyah dan Ibn ‘Arabi - Achmad Miftachul Ulum Ulum (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2022)
Islam is a religion that has an internal dimension called al-Ihsan. As an internal dimension, experts give different responses to the teachings of the Sufis. Some experts accept tasawwuf as an slamic teaching, and some experts criticize and even reject the teachings of tasawwuf because they think that the teachings of tasawwuf do not originate from Islam. Based on these findings, the writer will examine, examine and analyze from the point of view of the initiator and in terms of the style of thought, teachings and values ??of faith contained in the thoughts of Sufism figures both morally and spiritually such as Shaykh Abdul Qadir al-Jailani, tasawwuf 'irfani such as Rabi'ah al-Jailani. 'Adawiyyah and philosophical tasawwuf like Ibn 'Arabi. And a necessity, that Tasawwuf is a scientific discipline that was born from Islamic civilization, and the source of its teachings comes from the Qur'an and Hadith. This study is the result of a literature review where data is obtained from document study activities. This study proposes the finding that tasawwuf is a dimension of Islamic teachings which in this case can be seen and understood from the various patterns of thought of the figures in it. In practice, this research uses a qualitative descriptive approach as a research procedure that produces descriptive data. Data collection was carried out through text study activities, namely by registering library materials, searching, reading and recognizing and observing materials for further review and preparation for writing. Thus, this research report will contain excerpts of data to provide a presentation of the report. The results of the study show the thoughts of the character in question.